‘You would rather not fill your body with pills’—patient perspectives on polypharmacy and medication reviews by pharmacists in general practice - Josefine Graabæk Als; Janus Laust Thomsen; Sabrina Storgaard Sørensen; Søren Paaske Johnsen; Camilla Hoffmann Merrild (Scandinavian Journal of Primary Health Care)
Introduction Polypharmacy is widespread. The demographic shift toward older patients receiving multiple medications increases risk and drug-related problems in these patients.Objective To investigate patient perspectives on polypharmacy and the experienced effects of medication reviews by pharmacists in general practice.Methods Twenty-two semi-structured interviews with patients with polypharmacy (>5 medications) from 6 different general practice clinics in the North Denmark region. The interviewees were from the intervention arm of a randomized clinical trial and had received a medication review with a pharmacist in addition to the usual annual check-up in general practice. Participants were interviewed at baseline (no later than 2 weeks after the medication review) and again at follow-up (6 months after the medication review). The interviews were transcribed verbatim and thematically analyzed with an inductive approach.Results The patients’ narratives show that they face many difficulties in their everyday lives, making it hard for them to live up to society’s ideal of what it is to live a healthy life. The interviewees were generally positive toward the intervention and felt comfortable having a pharmacist conduct the medication review in their usual general practice clinic. Some interviewees gained more insight into their medication from the review.Conclusion Patient narratives give a comprehensive understanding of the challenges of polypharmacy. Having pharmacists conduct medication reviews in general practice could ensure more time and focus on patients and their medication management. The combined knowledge of physicians, nurses, and pharmacists regarding thorough polypharmacy management is recommended.